2017
DOI: 10.3389/fpls.2017.01077
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Water Stress Tolerance Mechanisms and Its Implications on Developing Biotechnology Solutions

Abstract: Sugarcane is a unique crop with the ability to accumulate high levels of sugar and is a commercially viable source of biomass for bioelectricity and second-generation bioethanol. Water deficit is the single largest abiotic stress affecting sugarcane productivity and the development of water use efficient and drought tolerant cultivars is an imperative for all major sugarcane producing countries. This review summarizes the physiological and molecular studies on water deficit stress in sugarcane, with the aim to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
121
0
22

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 210 publications
(329 reference statements)
2
121
0
22
Order By: Relevance
“…A tolerância de variedades de cana-de-açúcar ao estresse hídrico pode estar relacionada à herança genética das variedades, em que genes estariam associados à função adaptativa à privação de água em ambientes de reduzida umidade (NERKAR et al, 2018) e às respostas bioquímicas do sistema antioxidante enzimático, possibilitando que tais variedades tolerantes apresentem sistemas mais eficiente em condições de estresse (BOARETTO et al, 2014). Além destes mecanismos, Ferreira et al (2017) acrescentam a estratégia da cultura em manter alto estado de hidratação celular por meio de baixa condutância estomática durante a condição de estresse hídrico.…”
Section: Discussionunclassified
“…A tolerância de variedades de cana-de-açúcar ao estresse hídrico pode estar relacionada à herança genética das variedades, em que genes estariam associados à função adaptativa à privação de água em ambientes de reduzida umidade (NERKAR et al, 2018) e às respostas bioquímicas do sistema antioxidante enzimático, possibilitando que tais variedades tolerantes apresentem sistemas mais eficiente em condições de estresse (BOARETTO et al, 2014). Além destes mecanismos, Ferreira et al (2017) acrescentam a estratégia da cultura em manter alto estado de hidratação celular por meio de baixa condutância estomática durante a condição de estresse hídrico.…”
Section: Discussionunclassified
“…These findings may be explained by the role of Cauliflower Mosaic Virus 35S (CaMV 35S) promoter simultaneously in transgenic tobacco 18B1. CaMV 35S promoter is the most commonly constitutive, not tissue-and metal-specific promoter in plant biotechnology which has been successfully used to drive high levels of transgene expression (Ferreira et al, 2017). Plants in general have a range of potential mechanisms which might be involved in the heavy metal detoxification and thus confer a heavy metal tolerance property.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identifying and exploiting these tolerance mechanisms are fundamental to the development of new crop varieties resistant to drought stress. The overexpression of stress-tolerant genes using genetic engineering is one suitable approach to the development of drought-tolerant cultivars (Ferreira et al, 2017). It has been shown that the overexpression of a specific transcription factor (TF) involved in drought stress responses, dehydration responsive element binding (DREB2A) is able to improve drought tolerance in different plant species, including sugarcane, and it is highly induced under dehydration conditions (Bihani, Char, & Bhargava, 2011;Chen, Meng, Zhang, Xia, & Wang, 2008;Morran et al, 2011;Nakashima, Yamaguchi-Shinozaki, & Shinozaki, 2014;Qin et al, 2007;Reis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%